Peranan Hubungan Industrial - Jaminuddin Marbun (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
In general, the rich man becomes an entrepreneur and owns a company while those who run the company are workers and in general the entrepreneur sets up his company for profit. The advantage can be achieved in the company if high productivity and cost savings are incurred by the entrepreneur. Usually one of the ways of savings done by employers is not raising workers 'wages or adding workers' facilities such as not providing work clothes, not providing transportation money and others. The policy of the employer in his company that does not increase the wages of workers and facilities, even though productivity is demanded so that high will harm workers. Workers are generally in a weak position and this is due to more job seekers than available job openings. If vacancies are balanced with job seekers, the bargaining position between employers and workers has the same position. Weak workers in working relationships with employers requires government intervention as coaches, supervisors and protectors for workers and employers. The existence of interference from the government in employment relations for the production process of goods and or services is already an industrial relationship.